Comparative analysis of alkali basalt outcrops from Stóridalur at Eyjafjöll - Helga Kristín Torfadóttir 1992- (2017)
The Eyjafjallajökull volcano is considered to be the main locality for ankaramite in Iceland and is belived to be the index rock type of Eyjafjöll. It is an ultrabasic, porphyritic basanite rock type with clinopyroxene and olivine as phenocrysts and a plagioclase rich groundmass. Three representative samples were picked for this thesis from different outcrops from Stóridalur at Eyjafjallajökull volcano to study their texture and crystal content and the composition of the constituent phases. They were named EY 1, EY 2 and EY 3 and were collected in a quarry at the western flank. The hand specimen were observed followed by observation of thin sections in a perology microscope. The thin sections were then further studied in a Scanning Electron Microscopy (SEM) for observation of their chemical compositions. The samples turned out to be very similar and were porphyritic with intergranular groundmass and phenocrysts of plagioclase, olivine and clinopyroxene. The EY 3 sample stood out with a darker groundmass and had a greater ratio of groundmass relative to phenocrysts compared to the other two samples. Cluster of pyroxenes and plagioclase forming a coarse gabbro xenolith were found in samples EY 1 and EY 2. The xenolith found in EY 1 was chemically analysed by the SEM. The composition of the xenolith was distinct compared to the phenocrysts in the sample. The plagioclase in the xenolith had the lowest anorthite content with An52.29 compared to the other plagioclase phenocrysts that were most frequently An65-70. The pyroxene in the xenolith was richer in iron compared to the pyroxene phenocrysts but had the least amount of CaO and SiO2. Despite that many mafic rocks from the Eyjafjallajökull volcano were clasified as ankaramite, the detailed analyses of these samples suggested that they were in fact relatively evolved alkali basalts. These results suggest therfore, compared to what is thougt, that possibly the index rock type of Eyjafjöll might not nessicarily be ankaramite. Eyjafjallajökull er megineldstöð á ...